Methods of Calculating Energy Availability in Current Research: A Standardised Audit - Alicia E. Walker; Alannah K. A. McKay; Margot A. Rogers; Megan A. Kuikman; Kathryn E. Ackerman; Trent Stellingwerff; Louise M. Burke (Sports Medicine, 2026)
Abstract Introduction Energy availability (EA), defined as (energy intake [EI]—exercise energy expenditure [EEE])/fat free mass (FFM), has been studied in relation to athlete health and performance. We implemented a standardised audit protocol to assess the quality and characteristics of research that has calculated or manipulated EA in humans, and in particular, athletic populations. Methods Using the Smith et al. 2020 standardised protocol, we searched the PubMed database in June 2024 and October 2025 to identify human studies that directly assessed or manipulated EA. Exclusion criteria for our audit were indirect measurements of EA (questionnaire or survey), measurement of energy balance only, studies of diseased populations or reports in languages other than English. The included publications were assessed across the following metrics: population, athletic calibre, menstrual classification, study design and EA methodology. Results Of the 203 publications included in the audit, most included females (70%) or studied females alone (50%). High-performance athletes were well represented (45%; tiers 3–5) particularly among studies involving EA assessments. The audit system for evaluating the quality of menstrual status assessment found that 57% used techniques graded as ‘gold,’ ‘silver,’ and ‘bronze,’ yet a large proportion (43%) provided insufficient terminology or detail to classify female participants’ menstrual status (‘ungraded’). Most publications included naturally menstruating females (54%), while others included athletes with menstrual irregularities (28%) or those using hormonal contraceptives (18%). In studies observing EA ( n = 146), food records (82%) and metabolic equivalent scores (METs) (40%) were predominantly used to assess EI and EEE, respectively. Among intervention studies involving EA manipulations ( n = 57), most provided food to participants (77%) and determined EEE by physiologically derived methods (70%) such as indirect calorimetry or heart rate. Discussion/Conclusions High performance female athletes (tiers 3–5) are well-represented in EA research compared with other areas of sports science/medicine research. Despite the well-known association between EA and menstrual dysfunction, many EA studies failed to use high-quality methodology to describe or account for menstrual characteristics of female participants. The quality of such research will improve with better standardisation and characterisation of menstrual cycles of female participants and with further investigation of differences in the causes of and responses to low EA (LEA) exposure in male athletes. A standardised calculation of EA and best practice protocols for its assessment may improve the quality of EA studies, however, a need to focus on intervention studies rather than assessment of EA in free-living athletes is necessary to better understand the effects of LEA exposure on health and performance.